Bł. Johna Henry’ego kard. Newmana (1801–1890) teologia sumienia - Surmiak, Wojciech (Śląskie Studia Historyczno-Teologiczne, 2011)
Newman’s teaching of conscience unites originality and continuity. His originality manifests itself especially with regard to the Catholic theology of his era. Through his Anglican background, Newman belonged to a culture and the philosophical tradition, each of which was growing apart from the Catholic Church. Through dialogue – and often polemic – with his contemporaries, he was successful in handing on in a new language the contents of the faith and of religious experience, used concepts drawn from his own time, although not without renewing them profoundly.